Development Trend and Stability Analysis of Creep Landslide With Obvious Slip Zone Under Rainfall-Taking Xinchang Xiashan Basalt Slope as an Example - Bao, Chunyan; Zhan, Lingtao; Xia, Yingjie; Huang, Yongliang; Zhao, Zhenxing (Frontiers in Earth Science, 2022)
The creep slope is a dynamic development process, from stable deformation to instability failure. For the slope with sliding zone, it generally creeps along the sliding zone. If the sliding zone controlling the slope sliding does not have obvious displacement, and the slope has unexpected instability without warning, the harm and potential safety hazard are often much greater than the visible creep. Studying the development trend of this kind of landslide is of great significance to slope treatment and landslide early warning. Taking Xiashan village landslide in Huishan Town, Xinchang County, Zhejiang Province as an example, the landslide point was determined by numerical simulation in 2006. Generally, the landslide is a typical long-term slow deformation towards the free direction. Based on a new round of investigation and monitoring, this paper shows that there are signs of creeping on the surface of the landslide since 2003, and there is no creep on the deep sliding surface. The joint fissures in the landslide area are relatively developed, and rainfall infiltration will soften the soft rock and soil layer and greatly reduce its stability. This paper collects and arranges the rainfall data of the landslide area in recent 30 years, constructs the slope finite element model considering rainfall conditions through ANSYS finite element software, and carries out numerical simulation stability analysis. The results show that if cracks appear below or above the slope's sliding surface, or are artificially damaged, the sliding surface may develop into weak cracks. Then, the plastic zone of penetration is offset; In the case of heavy rain, the slope can unload itself under the action of rainfall. At this time, the slope was unstable and the landslide happened suddenly.